2017
DOI: 10.5455/njppp.2018.8.0728231072017
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric differences and gender variations in brainstem auditory evoked responses - A cross-sectional study in North Indian population

Abstract: Background: Gender is a known physiological variable reported to have influences on brainstem auditory evoked potential (BAEP) latencies irrespective of age. Anatomical differences have been suggested for such variations. Aims and Objectives: The present study was, hence, undertaken to evaluate the influence of gender on BAEP latencies and to assess the role of head size and body mass index (BMI) on BAEP responses and in gender variations. Materials and Methods: BAEP was recorded in 100 healthy adults (50 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…22 reported significantly shorter wave III and V along with I-III and I-V IPL in females as compared to males. Similar results were echoed by Gupta et al 23 , Soares et al 17 and Harinder et al 24 . Maurizi et al 25 reported statistically significant difference between boys and girls in wave III and V latency values and in III-V and I-V intervals below 2 years and seemed to increase with age.…”
Section: Gendersupporting
confidence: 79%
“…22 reported significantly shorter wave III and V along with I-III and I-V IPL in females as compared to males. Similar results were echoed by Gupta et al 23 , Soares et al 17 and Harinder et al 24 . Maurizi et al 25 reported statistically significant difference between boys and girls in wave III and V latency values and in III-V and I-V intervals below 2 years and seemed to increase with age.…”
Section: Gendersupporting
confidence: 79%